Enhancing Nurses' Participation in Implementing Evidence-Based Practice. Issue 2 (March 2015) - Pitkänen, Anneli; Alanen, Seija; Rantanen, Anja; Kaunonen, Marja; Aalto, Pirjo
<x xml:space="preserve">Abstract</x> The article gives an overview of a multidimensional project to enhance nurses' participation in implementing evidence-based practice (EBP) in one university hospital in Finland. The project provided an opportunity for many nurses to be an active part of the EBP process. Moreover, it provided an interesting opportunity to increase all nurses' awareness of EBP.